Hypothyroidism Review And Update (Journal of Pharmaceutical Negative Results, 2023)
Objective: review of scientific literature of a descriptive nature that provides an update on useful concepts for the diagnosis and timely treatment of Hypothyroidism. Brief description: Hypothyroidism in the United Kingdom presented 2%, in the United States it has a prevalence of 1.3% and in Latin America its incidence is up to 10% of the population, the most affected age group are women, the Secondary hypothyroidism and subclinical hypothyroidism affects older women between 60 and 65 years of age, unlike secondary hypothyroidism that harms women between 30 and 50 years of age more, this higher prevalence is associated with physiological and hormonal changes, on the contrary, Congenital Hypothyroidism It commonly harms neonates, in conclusion, each of these categories generate alterations in the hypothalamic-pituitary axis, which leads to a low production and secretion of Thyrotropin (TSH), and simultaneously decrease its biological activity in the thyroid gland. Conclusions: hypothyroidism is a pathology that may or may not present symptoms, if a long-term constant examination is not carried out, it can affect the life of the individual, therefore, it is important to keep updated in order to detect it in time for its correct treatment in patient benefit. The population most likely to develop it is from developing countries due to the lack of iodine in the diet, hypothyroidism can be classified into four categories, congenital hypothyroidism, primary hypothyroidism, secondary hypothyroidism, subclinical hypothyroidism and each of them reduces biological activity in the thyroid gland. Through this review, the incidence and prevalence of hypothyroidism in recent years was disclosed, the age group prevalent in people over 70 years of age, especially in the female gender, as far as its treatment depends on the type of hypothyroidism diagnosed.